Do Orthopaedic Oncologists Agree on the Diagnosis and Treatment of Cartilage Tumors of the Appendicular Skeleton? - Zamora, Tomas (Clin Orthop Relat Res, 2017)
BACKGROUND: Distinguishing a benign enchondroma from a low-grade chondrosarcoma is a common diagnostic challenge for orthopaedic oncologists. Low interrater agreement has been observed for the diagnosis of cartilaginous neoplasms among radiologists and pathologists, but, to our knowledge, no study has evaluated inter- and intraobserver agreement among orthopaedic oncologists grading these lesions using initial clinical and imaging information. Determining such agreement is important since it reflects the certainty in the diagnosis by orthopaedic oncologists. Agreement also is important as it will guide future treatment and prognosis, considering that there is no gold standard for diagnosis of these lesions. QUESTIONS/PURPOSES: (1) to determine inter- and intraobserver agreement among a multinational panel of expert orthopaedic oncologists in diagnosing cartilaginous neoplasms based on their assessment of clinical symptoms and imaging at diagnosis. (2) To describe the most important clinical and imaging features that experts use during the initial diagnostic process. (3) To determine interobserver agreement for proposed initial treatment strategies for cartilaginous neoplasms by this panel of evaluators. METHODS: Thirty-nine patients with intramedullary cartilaginous neoplasms of the appendicular skeleton of various histopathologic grades were selected and classified as having benign, low-grade malignant, or intermediate- or high-grade malignant neoplasms by 10 experienced orthopaedic oncologists based on clinical and imaging information. Additionally, they chose the three most important clinical or imaging features for the diagnosis of these neoplasms, and they proposed a treatment strategy for each patient. The Kappa coefficient (κ) was used to determine inter- and intraobserver agreement. RESULTS: Inter- and intraobserver agreements were only fair to good, κ = 0.44(95% CI, 0.41–0.48) and κ = 0.62 (95% CI, 0.52–0.72), respectively. The three factors most frequently identified as helpful in making the diagnosis by our panel were cortical involvement in 65% of evaluations (253/390), neoplasm size in 51% (198/390), and pain in 50% (194/390). The interobserver agreement for the proposed initial treatment strategy after diagnosis was poor (κ = 0.21; 95% CI, 0.18–0.24). CONCLUSIONS: This study showed barely fair interobserver and fair to good intraobserver agreement for grading of intramedullary cartilaginous neoplasms by orthopaedic oncologists using initial clinical and imaging findings. These results reflect the insufficient guidance interpreting clinical and imaging features, and the limitations of the systems we use today when making these diagnoses. In the same way, they generate concern for the implications that this may have on different treatment strategies and the future prognosis of our patients. Future studies should build on these observations and focus on clarifying our criteria of diagnosis so that treatment recommendations are standardized regardless of the treating institution or oncologist. LEVEL OF EVIDENCE: Level III, diagnostic study.